Effectiveness of Da‘wah bil-Lisān Training for Female Students of Baitul Abidin Darussalam Islamic Boarding School Ngebrak through the Seven-Minute Lecture Activity in the Process of Forming Students as Preachers - Faizal Nur Alwi (At-Takwin: Journal of Islamic Education Studies, 2025)
Preaching (Da’wah) is the responsibility of every Muslim, which can be carried out through speech, actions, or even through the heart. Da’wah can be conveyed to anyone, including oneself, as every individual needs reminders of goodness that can increase piety towards Allah SWT. The importance of da’wah, especially through spoken words, is recognized by the caretakers of Pondok Pesantren Baitul Abidin Darussalam. Therefore, the pesantren initiated a rotating short sermon (kultum) activity among the students (santri) as an effort to sharpen their preaching abilities. This study uses a qualitative method with a field approach conducted at Pondok Pesantren Baitul Abidin Darussalam, with the students as the research subjects. Data were collected through observation, interviews, and analysis adjusted to relevant theories. The results show that the regular kultum activity helps students develop their preaching skills and public speaking abilities. Although a small number of students still lack confidence and fluency in delivering their material, in general, most students have been able to present their kultum well. The topics covered are diverse, including subjects such as worship (ibadah), ethics (akhlak), Islamic jurisprudence (fiqh), and creed (aqidah), which also broaden the knowledge of both the listeners and the students who prepare the material.